Recurso efectivo. No lo constituye el juicio administrativo en Michoacán contra resoluciones que impliquen incumplimiento parcial de contratos de obra pública - Bautista Magaña, Hilda Liliana (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
The assumptions of origin of the Administrative Trial in the State of Michoacán contemplated in article 154, section VII and IX of the CJAM are not updated if only the partial or total non-compliance of a public works contract is challenged, by the individual, basically because There is no definitive administrative resolution from the authority regarding the interpretation and compliance of a contract of that nature that makes it appropriate for the state administrative instance to analyze its legality. Therefore, said paragraph limits the right of access to justice, in relation to the right to effective judicial protection protected by the various constitutional 17 and 25 of the ACHR, which guarantees the person the right to an effective remedy before judges or courts. competent authorities as a protective measure against violations of fundamental rights recognized by the Constitution, the law or in said Convention, even when such violation is committed by persons acting in the exercise of their official functions. In accordance with the provisions of Article 17 of the Constitution, in relation to Articles 2 and 25 of the ACHR, it is necessary to expand the jurisdiction of the TJAM by granting the contractor the possibility of complaining to the TJAM due to partial or total non-compliance with a contract. of public works, a circumstance that in turn allows the governed to have at their disposal a means of defense that provides access to jurisdictional protection in administrative matters, regardless of whether or not it is the resolution that puts an end to the procedure; thereby achieving harmonization of article 154, section VII and IX of the CJAM with the constitutional and conventional provisions already referred to.

Las causales de procedencia del Juicio Administrativo en el Estado de Michoacán contemplados en el artículo 154, fracción VII y IX del CJAM no se actualizan si solamente se impugna el incumplimiento parcial o total de un contrato de obra pública, por parte del particular, básicamente porque no existe una resolución administrativa de carácter definitivo de la autoridad en materia de interpretación y cumplimiento de un contrato de esa naturaleza que haga procedente la instancia administrativa estatal para analizar su legalidad. Por lo tanto, dicho numeral limitan el derecho de acceso a la justicia, en relación con el de tutela judicial efectiva amparado en el diverso 17 constitucional y 25 de la CADH que garantiza a la persona el derecho a un recurso efectivo ante los jueces o tribunales competentes como una medida protectora ante violaciones de derechos fundamentales reconocidos por la Constitución, la ley o en dicha Convención, aun y cuando tal violación sea cometida por personas que actúen en ejercicio de sus funciones oficiales. Atendiendo a lo dispuesto por el artículo 17 constitucional, en relación con el 2 y 25 de la CADH, es necesario se amplie la competencia del TJAM al conceder la posibilidad al contratista de inconformarse ante el TJAM con motivo del incumplimiento parcial o total de un contrato de obra pública, circunstancia que permite a su vez que el gobernado tenga a su alcance un medio de defensa que le proporcione acceso a la tutela jurisdiccional en materia administrativa, con independencia de que sea o no la resolución que le ponga fin al procedimiento; logrando con ello armonizar el artículo 154 fracción VII y IX del CJAM con las disposiciones constitucionales y convencionales ya referidas.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2025-0065; Derecho administrativo; Acceso; Justicia; Efectivo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19227